MANAGEMENT OF HYPERCOAGULABLE STATE DURING PREGNANCY. PROPHYLACTIC USAGE OF LOW MOLECULAR WEIGHT HEPARIN (LMWH) - Sihana Ahmeti Lika; Nexhibe Nuhii; Merita Dauti; Ledjan Malaj (European Scientific Journal, ESJ, 2015)
The main objective of this study is to analyze the prophylactic usage of low molecular weight heparin, in women during the period of pregnancy. A retrospective study was undertaken during 01 January – 31 December of 2013, in the Department of Gynecology and Obstetrics, at Clinical Hospital in Tetovo. Data were collected for the following: patient demographics, week and month of pregnancy, number of pregnancies for each patient, duration of hospital stay, clinical and laboratory investigations, diagnosis, drug details; which include the name of the drug, dosage form, dose frequency, total cost of the drug, the amount of each given ampoule application and the cost for the entire period of hospitalization. Among of 643 women whom were prescribed LMWH, 144 of them were found hypercoagulable. The majority of patients given LMWH were aged 25-30 years (56.25 %). For the biggest number of patients, this was their first pregnancy (70.83%). Earliest phase of using LMWH was the second month of pregnancy, respectively sixth week. Patients during the ninth month, apear to be more affected by hypercoagulable statete. 56 (38.89 %) women were in the ninth month of pregnany. Fraxiparine (nadroparin calcium) 3800 IU anti-Factor XA in 0.4 ml was the most prescribed anticoagulant, 64 (44.44 %) patients received this therapy. From the total number of 144 patients, only 4 of them received LMWH twice a day.